Interstitial lung disease and anti-Jo-1 antibodies: difference between acute and gradual onset. Issue 1 (8th June 2007) - Tillie-Leblond, I; Wislez, M; Valeyre, D; Crestani, B; Rabbat, A; Israel-Biet, D; Humbert, M; Couderc, L J; Wallaert, B; Cadranel, J
Abstract : Aim: A multicentre retrospective study was undertaken to examine patients with interstitial lung disease (ILD) with the initial clinical manifestation of an anti-synthetase syndrome (anti-Jo-1 antibodies), and to analyse the characteristics and long-term outcome of these patients according to their clinical presentation (acute or gradual onset), treatment and adverse events related to treatment. Methods: 32 patients, 15 (47%) presenting with acute onset and associated respiratory insufficiency (group A) and 17 (53%) with gradual onset (group G) were examined. Myositis was diagnosed at admission in only 31% of cases and was observed during follow-up in 56% of cases, but the prevalence did not differ between the two groups. Results: Fever and radiological patterns including diffuse patchy ground-glass opacities, basal irregular lines and consolidation on high-resolution CT scan were more frequent in group A than in group G. More patients in group G had neutrophils in the bronchoalveolar lavage fluid and autoantibodies other than anti-Jo-1 (rheumatoid factor, anti SSa/SSb) than in group A. The percentage of patients in whom the ILD improved at 3 months was significantly higher in group A than in group G (13/15 vs 9/17; p = 0.006). In contrast, after 12 months, most patients with ILD progression were in group A and were treated with corticosteroids alone. A combination of corticosteroids and an immunosuppressive drug was required in most cases (84%) at the end of the follow-up period. Severe adverse effects of treatment were observed and varicella zoster virus infection was frequent. Conclusions: Early testing for anti-synthetase antibodies, particularly anti-Jo-1, and creatine kinase determination are useful procedures in patients presenting with ILD. Treatment with corticosteroids and immunosuppressive drugs is required in most patients. At the end of the study, around two-thirds of patients had stable ILD while the other third had disease progression with respiratory insufficiency.